The Influence of Sharia Capital Market, Sharia Bonds (Sukuk), and BI Rate on Gross Domestic Products (GDP) in Indonesia - Gebi Gita Marsi; Dyah Titis Kusuma Wardani (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to determine what affect GDP (Gross Domestic Product) in constant Indonesian prices. The dependent variable used is GDP (Gross Domestic Product), and the independent variables are Islamic stocks, Islamic mutual funds, Islamic bonds (Sukuk), and the BI rate. The data used in this study are monthly during the period 2016: 1-2018: 12 sourced from OJK, BI, and Ministry of Home Affairs. The estimation tool used in this study is the Vector Error Correction Model (VECM) using E-views 7.0. Estimation results show that in the short term, the GDP variable (Gross Domestic Product) itself, Islamic stocks, BI rate, and Islamic mutual funds significantly affect GDP (Gross Domestic Product). In the long run, the estimation results show that sharia stock variables and sharia mutual funds have a significant effect on GDP (Gross Domestic Product). While the sharia bond variable (Sukuk) and the BI rate do not significantly affect GDP (Gross Domestic Product). VECM estimation results in this study also produce important Says, namely IRF (Impulse Response Function) and VDC (Variance Decomposition).